Intravitreal injection of the Galectin-3 inhibitor TD139 provides neuroprotection in a rat model of ocular hypertensive glaucoma - Anne Rombaut; Rune Brautaset; Pete A. Williams; James R. Tribble (Molecular Brain)
Abstract Neuroinflammation is a significant contributor to the pathology of glaucoma. Targeting key-mediators in this process is a realistic option to slow disease progression. Galectin-3 is a β-galactoside binding lectin that has been associated with inflammation in both systemic and central nervous system diseases. Elevated Galectin-3 has recently been detected in multiple animal models of glaucoma and inhibiting Galectin-3 using an intravitreal injection of TD139 (a Galectin-3 small molecule inhibitor) is neuroprotective. We queried whether this neuroprotective effect was translatable to another animal model and species. TD139 was intravitreally injected, in a rat ocular hypertensive model of glaucoma, 3 days after the induction of ocular hypertension (at peak intraocular pressure). Retinal ganglion cell survival and glial morphological markers were quantified. The degeneration of retinal ganglion cells was prevented by TD139 injection, but gross glial markers remained unaffected. These data confirm that the intravitreal injection of TD139 is neuroprotective in a rat ocular hypertensive model of glaucoma, while suggesting that the inhibition of Galectin-3 is not sufficient to alter the gross inflammatory outcome.